Healthcare Transformation Through Medical Technology: Opportunities, Challenges, and Implementation Strategies - Sarif, Nurul Husna Binti; Issalillah, Fayola (Metromedia, 2022)
Technological advancements have driven significant transformations in healthcare, particularly through the adoption of telemedicine and digital medical devices. These technologies enable wider access to medical services, improve health system efficiency, and speed up diagnosis and treatment. Studies show that telemedicine has overcome geographical barriers and expanded the reach of healthcare services, especially for people in remote areas. In addition, the use of digital-based medical devices has improved monitoring of patient conditions and supported more accurate medical decision-making. However, the implementation of medical technology still faces various challenges. Limited digital infrastructure in some regions hinders the widespread implementation of telemedicine. In addition, the access inequality between socio-economic groups remains a significant issue, as not all individuals have access to adequate digital devices. Non-uniform regulations also slow down the adoption of this technology, especially in the aspects of data protection and legal approval. This research highlights the opportunities and challenges in the application of medical technology and the strategies that can be employed to optimize its benefits. The results of this study are expected to provide insights for policymakers and health practitioners to develop a more inclusive and sustainable technology-based healthcare system.